Biochemical Investigation of Oil of Eugenia carophyllata - Khan, M.R.; Iqbal, J. (Asian Journal of Chemistry, 2011)
The oil of Eugenia carophyllata was extracted with petroleum ether and ethanol. The oil was subsequently investigated for its fundamental properties and antibacterial activity. The homogenized seeds and the residue of Eugenia carophyllata left after extraction were also checked only for antibacterial activity. It was observed that the homogenized seeds were active against Escherichia coli and Staphylococcus aureus. The oil extracted with petroleum ether and ethanol were active against both organisms, while the residue left after extraction with petroleum ether was active against Escherichia coli but was inactive against Staphylococcus aureus. The residue left after extraction with ethyl alcohol was active against both the organisms. The physical and chemical properties of oils were also determined and compared. The oils extracted were also subjected to thin layer chromatography to determine the polar and non-polar lipids.